Design, development and characterization of synthetic Bruch's membranes. (December 2017) - Surrao, Denver C.; Greferath, Ursula; Chau, Yu-Qian; Skabo, Stuart J.; Huynh, Mario; Shelat, Kinnari J.; Limnios, Ioannis J.; Fletcher, Erica L.; Liu, Qin
Graphical abstract: Abstract: Age-related macular degeneration (AMD) is a leading cause of blindness, and dry AMD has no effective treatment. Retinal constructs comprising retinal pigment epithelium (RPE) cells supported by electrospun scaffolds have been investigated to treat dry AMD. However, electrospun scaffolds studied to-date do not mimic the structural microenvironment of human Bruch's membrane (BM), essential for native-like RPE monolayers. The aim of this study was to develop a structurally biomimetic scaffold designed to support a functional RPE monolayer, comprising porous, electrospun nanofibrous membranes (ENMs), coated with laminin, mimicking the inner collagenous layer (ICL) and basal RPE lamina respectively, the cell supporting layers of the BM. In vitro evaluation showed 70 nm PLLA ENMs adsorbed high amounts of laminin and supported functional RPE monolayers, exhibiting 3D polygonal-cobblestone morphology, apical microvilli, basal infoldings, high transepithelial resistance (TER), phagocytic activity and expression of signature RPE markers. 70 nm PLLA ENMs were successfully implanted into the subretinal space of RCS-rdy+p+/LAV rats, also commonly know as rdy rats. At week 4, in the absence of immunosuppressants, implanted PLLA ENMs were surrounded by a significantly low number of activated microglial cells, compared to week 1, indicating no adverse long-term immune response. In conclusion, we successfully designed and tested ENMs emulating the RPE cell supporting layers of the BM, and found 70 nm PLLA ENMs to be best suited as scaffolds for fabricating retinal constructs. Statement of Significance: Age related macular degeneration (AMD) is a leading cause of vision loss in the developed world, with an increasing number of people suffering from blindness or severe visual impairment. Transplantation of retinal pigment epithelium (RPE) cells supported on a synthetic, biomimetic-like Bruch's membrane (BM) is considered a promising treatment. However, the synthetic scaffolds used do not mimic the microenvironment of the RPE cell supporting layers, required for the development of a functional RPE monolayer. This study indicated that porous, laminin coated, 70 nm PLLA ENMs supported functional RPE monolayers, exhibiting 3D polygonal-cobblestone morphology, apical microvilli, basal infoldings, high transepithelial resistance (TER), phagocytic activity and expression of signature RPE markers. These findings indicate the potential clinical use of porous, laminin coated, 70 nm PLLA ENMs in fabricating retinal constructs aimed at treating dry AMD.